Monitoring pro-cyclicality under the capital requirements directive: preliminary concepts for developing a framework - Nancy Masschelein (National Bank of Belgium, 2007)
This paper provides an overview of the questions that will need to be addressed in order to determine whether increased cyclicality in capital requirements will exacerbate the pro-cyclicality in the financial system. Many central banks have raised concerns about the potential cost of procyclicality that could come with the Basel II framework, which will be implemented in the EU via the Capital Requirements Directive (CRD). Previous capital adequacy rules required banks to hold a minimum amount of capital for each loan, regardless of the different risks involved. The main objective of the Basel II framework/CRD is to make capital requirements more risk-sensitive. Therefore, by construction, the capital requirements under the CRD will be more cyclical than under the previous rules. This raises two questions. First, does it matter whether regulatory capital requirements fluctuate more than before if banks' (lending) behaviour is driven by other capital considerations (for example economic capital) ? Second, if it does matter, what impact will this have on the economic cycle?
Keywords: G18; E32; 330; Basel II/CRD; pro-cyclicality; Basler Akkord; Basler Akkord; EU-Bankrecht; EU-Staaten